Sosialisasi Mencegah Informasi HOAX Terhadap Kehidupan Sosial Masyarakat (SMA Negeri 3 Tidore) - Salkin Lutfi; Alfanugrah A. Hi. Usman; Saiful Do. Abdullah (Jurnal Nusantara Berbakti, 2023)
The current development of information technology issued by both individuals and business entities through social and electronic media when it has been sent and read by many people can affect the emotions, feelings, thoughts and even the actions of a person or group. It is very unfortunate if the information conveyed is inaccurate information, moreover the information is false information (hoax) with very provocative titles leading readers and recipients to negative opinions. Negative opinions, slander, hate speech that are received and attack parties or make people afraid, threatened and can harm the party being reported so that they can damage reputation and cause material losses (Aan erlansari, 2020). Many people use the internet as a daily necessity in finding information on social media, especially children who are still in their teenage phase. On the other hand, the spread of HOAX on social media has resulted in hate speech and negative elements in people's social life. In this case the government formed the Anti-Hoax Momentgas, but to counter HOAX the government is not strong enough to work alone, so in this service the author wants to make socialization to prevent HOAX information on people's social life, (SMAN 3 Tidore Kepulauan).